Determination of Total Protein Content of Bacterial Cells by SYPRO Staining and Flow Cytometry - Zubkov, Mikhail V. (American Society for Microbiology, 1999)
An assay has been developed for measuring protein biomass of marine planktonic bacteria by flow cytometry. The method was calibrated by using five species of Bacteria (an Arcobacter sp., a Cytophaga sp., an Oceanospirillum sp., a Pseudoalteromonas sp., and a Vibrio sp.) recently isolated from seawater samples and grown in culture at different temperatures. The intensity of SYPRO-protein fluorescence of these bacteria strongly correlated with their total protein content, measured by the bicinchoninic acid method to be in the range of 60 to 330 fg of protein cell(−1) (r(2) = 0.93, n = 34). According to the calibration, the mean biomass of planktonic bacteria from the North Sea in August 1998 was 24 fg of protein cell(−1).